2016
DOI: 10.15694/mep.2016.000133
|View full text |Cite
|
Sign up to set email alerts
|

“My way of giving something back”: Patient and carer experiences of involvement in medical education

Abstract: BackgroundPatient involvement initiatives in medical education traditionally focus exclusively on the rationale, need, and potential benefits to learners in developing patient-centred practice. ObjectivesThis study explores the impact of involvement on patient educators working in medical education. MethodA mixed methods approach was used to generate data for content analysis. Participants completed a questionnaire (n= 49) and were then invited for a follow-up interview (n=20), both methods explored views on i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…A common subtheme identified is patient educators showing gratitude for their care and wanting to give something back . This is a consistent finding in the literature, with several articles citing patients who want to be involved in medical teaching so they can repay the care they were provided while being ill [ 3 , 16 - 19 ]. The educators’ altruism has two components: one aimed at the hospital and staff where they have received care and a wider one where patients believe being involved in teaching medical students will provide enhance and broaden students’ experience, influence practice and help the wider community.…”
Section: Discussionsupporting
confidence: 70%
“…A common subtheme identified is patient educators showing gratitude for their care and wanting to give something back . This is a consistent finding in the literature, with several articles citing patients who want to be involved in medical teaching so they can repay the care they were provided while being ill [ 3 , 16 - 19 ]. The educators’ altruism has two components: one aimed at the hospital and staff where they have received care and a wider one where patients believe being involved in teaching medical students will provide enhance and broaden students’ experience, influence practice and help the wider community.…”
Section: Discussionsupporting
confidence: 70%
“…Notwithstanding the unpredictability of emotions in storytelling, the participants in this study offered an overwhelmingly positive view of their storytelling experience. The existing body of research on involving patients in various initiatives similarly emphasises the perceived positive aspects of their role, such as giving back to future health professionals and making valued contributions to student learning . The educational successes of programmes that involve patients have also been widely broadcast .…”
Section: Discussionmentioning
confidence: 99%
“…2,5,6,11 To date, researchers have focused primarily on patients' perspectives on their involvement in medical education rather than in the education of all HCPs. For example, Fielden and O'Rourke 12 explored patients' motivations for becoming involved in medical education at a medical school and the impact of this involvement on them. They found that patients participated in medical education because it provided them with a means to reflect on their conditions and experiences and that it positively impacted their health and well-being.…”
Section: Introductionmentioning
confidence: 99%
“…They found that patients participated in medical education because it provided them with a means to reflect on their conditions and experiences and that it positively impacted their health and well-being. 12 Similarly, Stacy and Spencer 13 focused on patients' perceptions of being involved in medical students' community-based projects and noted that patients viewed themselves as teachers who could educate medical students on their conditions and help them develop their professional skills and attitudes. Moreover, Jackson, Blaxter, and Lewando-Hundt 14 investigated patients' views on their active involvement in medical education.…”
Section: Introductionmentioning
confidence: 99%